Rock In The Box - To Know You Is To Love You - John F. Abel (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1970)
Personal gain seems to be the most powerful incentive to economic progress. One of my first exposures to this phenomenon was the comparison between company stopes and leaser's stopes in a vein gold mine. The company stopes were 4 to 6 ft wide, whereas the leaser's stopes were so narrow that in some places one could not turn around. The company leased only that ground it felt was marginal to mine with day's- pay miners, but by skillful, careful and energetic mining, the leasers managed in most cases to make money for themselves and the company. The Hurting Truth This capitalist system, which puts a premium on successful risk taking, is under attack. Not that it hasn't been under attack all along. What hurts and angers us at this time is that the attack comes from the children of the system-its youth. Such blasphemy should, of course, be eradicated, root and branch. Or should it? Are we hurt in part because some of the things they say are true?